Experimental investigation, model validation and application of twin-screw expanders with different built-in volume ratios. (15th January 2021) - Dawo, Fabian; Eyerer, Sebastian; Pili, Roberto; Wieland, Christoph; Spliethoff, Hartmut
Abstract: Organic Rankine Cycles (ORC) are a promising technology to generate power from low temperature heat sources and can therefore help transform current energy systems into renewable ones. However, ORCs are often affected by a wide range of operating conditions with a high share of part load operation. Therefore, detailed component models are necessary for the design of these ORC modules. In this study, systematical experimental investigations were conducted on two identical twin-screw expanders with different built-in volume ratios. The expander measurements covered the entire operational range of the ORC test rig and the expander by methodically varying rotational speed, mass flow, inlet pressure and superheating at constant expander outlet pressure. The experimental data is then utilized to validate a semi-empirical model of the twin-screw expander. Subsequently, the validated expander model is used to determine the optimum built-in volume ratio of an expander supplied by a wide range of heat source temperatures and mass flows and fluctuating heat source mass flows. The experimental results show increasing filling factors with decreasing rotational speeds and maximum isentropic efficiencies at intermediate pressure ratios. The maximum isentropic efficiency achieved is 64 %. The model validation shows a satisfactory accuracy of the model within a 10 % deviation for data with the same built-in volume ratio. Changing the built-in volume ratio requires the adjustment of the model parameters, because the amount of internal leakage changes. The simulations used to determine the optimum built-in volume ratio show the importance of the selection of the optimum built-in volume ratio in dependency of the heat source. Furthermore, particular attention has to be paid to the operational range of the expander (mainly the rotational speed), since it can significantly limit the power output. Highlights: Experimental data of two twin-screw expanders operated with R1233zd(E). Two different built-in volume ratios are experimentally investigated. Validation of a twin-screw expander model with experimental data. Optimization of the built-in volume ratio for varying heat source conditions.